DISPARITAS KESIAPAN SEKOLAH NEGERI DAN SEKOLAH SWASTA DALAM MENINGKATKAN MUTU PENDIDKAN VOKASI - Umi Kulsum (JS (JURNAL SEKOLAH), 2020)
Abstract: Disparity in the Readiness of Public Schools and Private Schools in Improving the Quality of Vocational Education. The purpose of this study is to determine the disparity in public school and private school preparedness in vocational schools as an effort to improve the quality of vocational education. Research conducted includes governance of institutions, teachers and education personnel, learning curriculum and graduate work. The study was conducted at one of the state vocational schools and private vocational schools in Malang Raya. This research is a qualitative descriptive study using a phenomenological approach. Data collection techniques through observation and interviews. The results showed differences in terms of institutional governance, teachers and education personnel, learning curriculum, and graduate work. The conclusion of this study is the disparity in the quality of education because the government in implementing policies in the field of education has not been evenly distributed. Thus improving the quality of vocational education can be realized. Keywords: disparity, school readiness, quality of vocational education Abstrak: Disparitas Kesiapan Sekolah Negeri dan Sekolah Swasta dalam Meningkatkan Mutu Pendidikan Vokasi. Tujuan penelitian ini adalah mengetahui disparitas kesiapan sokolah negeri dan sekolah swasta di lingkungan SMK sebagai upaya dalam peningkatan mutu pendidikan vokasi. Penelitian yang dilakukan meliputi tata kelola lembaga, guru dan tenaga kependidikan, kurikulum pembelajaran, serta kebekerjaan lulusan. Penelitian dilakukan di salah satu SMK negeri dan SMK swasta di Malang Raya. Penelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan pendekatan fenomenologi. Teknik pengumpulan data dengan observasi dan wawancara. Hasil penelitian menunjukkan adanya perbedaan  ditinjau dari tata kelola lembaga, guru dan tenaga kependidikan, kurikulum pembelajaran, serta kebekerjaan lulusan. Kesimpulan dari penelitian ini adalah adanya disparitas mutu pendidikan karena pemerintah dalam menerapkan kebijakan bidang pendidikan belum merata. Dengan demikian peningkatan mutu pendidikan vokasi bisa terwujud.Kata kunci: disparitas, kesiapan sekolah, mutu pendidikan vokasi